Resolving two centuries of mistaken identity: Reinterpretation of Papilio marcus Fabricius, 1787 (Lepidoptera: Nymphalidae, Hesperiidae) - Nakahara, Shinichi; Zilli, Alberto; Calhoun, John V.; Espeland, Marianne; Padrón, Pablo Sebastián; Grishin, Nick V. (Zootaxa, 2022)
Here, we untangle an oversight surrounding the application of the name Papilio marcus Fabricius, 1787 (Hesperiidae: Hesperiinae), currently in Troyus Warren & Turland, 2012, which has eluded taxonomists for nearly two centuries. First, we note that P. marcus is a junior primary homonym of Papilio marcus Schaller, 1785, a species currently in Morpho Fabricius, 1807 (Nymphalidae: Satyrinae). Second, we designate a lectotype for P. marcus Fabricius, 1787, and recognize it as conspecific with Papilio phyllus Cramer, 1777, a species currently in Vettius Godman, 1901. Therefore, P. marcus is also a junior subjective synonym of V. phyllus (new synonym). Third, aided by genomic sequencing of the lectotype of Vettius phyllides Röber, 1925, we find that this species is not conspecific with V. phyllus and represents instead a valid species of Troyus Warren & Turland, 2012, so that the relative epithet, currently considered as a junior subjective synonym of P. marcus, has to be reappreciated as Troyus phyllides (reinstated status, new combination). Moreover, T. phyllides is apparently the species that has been misidentified as P. marcus since 1832. As a result of this study, the name P. marcus Fabricius nec Cramer falls in synonymy with P. phyllus (currently in Vettius), and the species currently known as T. marcus becomes Troyus phyllides.